CHARACTER EDUCATION BASED ON THE QADIRIYAH NAQSYABANDIYAH THARĪQAH IN ISLAMIC VOCATIONAL HIGH SCHOOL - Khoiruddin, M Arif; Masrukin, Ahmad (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this study is to reveal how character education is built based on tarekat as a self-strengthening student not only physically but also mentally with the aim of the character being formed from within the student. This study used a qualitative phenomenological approach. Obtained the data sources from the head of the foundation, the principal, the head of student affairs, the director of religious extracurricular activities, teachers and parents, and students who participated in mujahadah activities. The study results reveal the formation of character in the cognitive aspect using a teaching model or ta'lim by providing knowledge of the nature of faith, worship, ethics, as well as wisdom and wisdom. Sharpening the psychomotor aspects of students using the ta'dib or habituation model to improve themselves and provide awareness to students and affective aspects with the irsyad model or spiritual guidance in forming attitudes from within not only with feelings and emotions but added with strengthening the spiritual element or spirituality through dhikr and mujahadah activities which are believed to be a process of character building from within to become better and raise awareness from within students